2020
DOI: 10.21005/asp.2019.18.4.04
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage time and temperature on the quality of natural yoghurt

Abstract: Cooling temperature and storage time have a significant effect on the quality of natural yogurts and their durability in retail. The aim of the study was to perform a physicochemical, microbiological and organoleptic assessment of commercial yogurt, immediately after purchase and during 3 weeks of storage at 2°C and 8°C. The following physicochemical parameters were measured: pH, titratable acidity, color (CIEL a*, b*) and basic chemical composition. The organoleptic assessment included the general appearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…In contrast, as pH values were dropped during the first 7 days, a slight increase was noted on the 14 th day of storage. This result agrees with the previous study conducted by Jakubowska and Karamucki (2020) (Turnbull et al, 2005), which can dilute the produced acidity. An assessment was made of the acidity levels of the strained yogurt supplemented with different concentrations of SLSH.…”
Section: Physicochemical Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, as pH values were dropped during the first 7 days, a slight increase was noted on the 14 th day of storage. This result agrees with the previous study conducted by Jakubowska and Karamucki (2020) (Turnbull et al, 2005), which can dilute the produced acidity. An assessment was made of the acidity levels of the strained yogurt supplemented with different concentrations of SLSH.…”
Section: Physicochemical Analysissupporting
confidence: 93%
“…Sady et al (2007) reported that the concentration of S. thermophilus and L. bulgaricus in natural yogurt was increased slightly during the first three days, then decreased to the lowest level after 14 days storage. Also, the reduction in S. thermophilus was higher than L. bulgaricus, as S. thermophilus is less tolerant to high acidity, while L. bulgaricus strains can survive in an environment with a pH below 4.0 (Jakubowska and Karamucki, 2020). Generally, the yogurt whey containing large numbers of S. thermophilus, and L. bulgaricus, was lost during the production of the strained yogurt.…”
Section: Bacterial Enumerationmentioning
confidence: 99%
“…In our research, when we examined the color components of the fermented sheep milk beverages, no statistically significant change in their brightness (L*) was found over the 21 days of the storage period. Jakubowska and Karamucki obtained similar results for retailed cow’s milk yogurts [ 44 ]. When the fermented milk drinks in our study were compared on a specific storage day, it was found that Greek-type yogurt had the highest value of this parameter just after production and the lowest on day 21.…”
Section: Discussionmentioning
confidence: 73%
“…Magnesium is another electrolyte present in the blood and therefore would be expected to increase in response to water deprivation. Jakubowska et al (2017) exposed birds to 3 pretransport fasting conditions for a 12-h period. The treatment group of birds deprived of both feed and water showed significantly lower blood magnesium concentrations than the treatment with only feed withdrawn and continued access to water.…”
Section: Resultsmentioning
confidence: 99%